Impact of Dysmenorrhea on Female Adolescents - Karmacharya, Poonam; Bhattarai, Anshu; Tiwari, Indu; Singh, Surjit (Journal of College of Medical Sciences-Nepal, 2022)
Introduction Dysmenorrhea is a common condition that usually presents itself with cramps or a dull ache, mostly in the abdominal region. Alongside the cramps, it is also common to suffer from other symptoms such as nausea, diarrhoea, constipation, mood swings and headaches. Dysmenorrhea has been considered a leading cause of occupational and college absenteeism among women, yet little is known about its actual impact. The objective of this study is to understand the impact of dysmenorrhea in the young female medical students. Methods A cross-sectional study was carried out in 100 undergraduate students of Manipal college of Medical Sciences, Pokhara, Nepal. Standardized Self-reporting questionnaires were used to obtain relevant data. Data entry and analysis were done in SPSS 20. Results Out of 100 females, Majority of girls, 84 out of 100 reported different grades of dysmenorrhea. The study also showed strong association of dysmenorrhea with the family history and the severity of dysmenorrhea was highly associated with college absenteeism and regularity of the cycle. (p-value<=0.005). Other symptoms like stomach cramp, anxiety, irritability, difficult in concentration and insomnia were also significantly associated with dysmenorrhea (p<0.005) while stress was strongly associated with the dysmenorrhea. (p<0.000). However, Backaches, painful breast, nausea, skin disorders, appetite and forgetfulness were not associated with dysmenorrhea (p>0.005). Conclusions Dysmenorrhea is found to be highly prevalent and has a negative impact on physical, social and academic activities of medical female students. The effect of dysmenorrhea is very wide, therefore managing the condition is very important.